ChemInform Abstract: Copper‐Catalyzed Oxidative Ring Closure of ortho‐Cyanoanilides with Hypervalent Iodonium Salts: Arylation‐Ring Closure Approach to Iminobenzoxazines. Issue 26 (June 2015) - Aradi, Klara; Novak, Zoltan
Abstract A novel, highly modular synthetic methodology with high functional group tolerance is developed for the construction of iminobenzoxazine derivatives from ortho‐cyanoanilides and diaryliodonium triflates via an oxidative arylation—cyclization path.